PENGARUH KEMANDIRIAN TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG - Noviza Indar Sulistiani; Mara Yunika; Vicky F Sanjaya (Business and Enterpreneurship Journal (BEJ), 2023)
The purpose of this study was to determine the effect of independence on entrepreneurial interest in Raden Intan Lampung State Islamic University students. The data used in this study were primary data. Furthermore, the data collection technique used in this study was a survey using Google form to collect data. . In this study the researchers used the f test method and the coefficient test with the help of the smart plss program version 2. Based on the results of the research, the R² value lies at 0 R² 1, an R² value close to 1, which means the model is getting better. Meanwhile, the value of R² which is zero means that there is no relationship between the dependent variable and the explanatory variable. From the table, with the location of R² 1 with a value of 0 0.682 1, this means that the variance of Independence is able to explain the variance of Interest in Entrepreneurship of 68 .2%, while the remaining 31.8% is explained by other variables outside the model. Keywords :Independence, and Entrepreneurial Interest